2018
DOI: 10.1128/jvi.01677-17
|View full text |Cite
|
Sign up to set email alerts
|

Type III Interferon Restriction by Porcine Epidemic Diarrhea Virus and the Role of Viral Protein nsp1 in IRF1 Signaling

Abstract: Type III interferons (IFNs) play a vital role in maintaining the antiviral state of the mucosal epithelial surface in the gut, and in turn, enteric viruses may have evolved to evade the type III IFN responses during infection. To study the possible immune evasion of the type III IFN response by porcine epidemic diarrhea virus (PEDV), a line of porcine intestinal epithelial cells was developed as a cell model for PEDV replication. IFN-λ1 and IFN-λ3 inhibited PEDV replication, indicating the anti-PEDV activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
180
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(190 citation statements)
references
References 80 publications
(122 reference statements)
8
180
2
Order By: Relevance
“…Consistent with the previous reports (Brosnahan and Brown, 2012;Vergauwen, 2015), the IPEC-J2 cells appeared to consist mostly of intestinal absorptive (non-secretory) villous enterocytes. However, a recent study reported that the non-homogeneity of the IPEC-J2 cells that they observed might be associated with little or no susceptibility of the cells to PEDV infection, and that only the subcloned IPEC-J2 cells became susceptible to PEDV infection (Zhang et al, 2018). Nevertheless, it is critical to note that IPEC-J2 cells have been infected successfully with PEDV, as reported previously (Lin et al, 2017;Shi et al, 2017;Zhao et al, 2014).…”
Section: Ipec-j2 Cells Appeared To Consist Mostly Of Intestinal Absormentioning
confidence: 60%
“…Consistent with the previous reports (Brosnahan and Brown, 2012;Vergauwen, 2015), the IPEC-J2 cells appeared to consist mostly of intestinal absorptive (non-secretory) villous enterocytes. However, a recent study reported that the non-homogeneity of the IPEC-J2 cells that they observed might be associated with little or no susceptibility of the cells to PEDV infection, and that only the subcloned IPEC-J2 cells became susceptible to PEDV infection (Zhang et al, 2018). Nevertheless, it is critical to note that IPEC-J2 cells have been infected successfully with PEDV, as reported previously (Lin et al, 2017;Shi et al, 2017;Zhao et al, 2014).…”
Section: Ipec-j2 Cells Appeared To Consist Mostly Of Intestinal Absormentioning
confidence: 60%
“…The viral proteins E and N upregulated IL-8 expression by inducing endoplasmic reticulum stress and subsequent activation of the NF-kB pathway [97,98]. PEDV can evade host innate immune responses via at least 11 proteins (nsp1, nsp3, nsp5, nsp7, nsp14, nsp15, nsp16, ORF3, E, M, and N) that function as interferon (IFN) antagonists [99][100][101][102]. Identification of the virus-encoded IFN antagonists and understanding their mechanism of action may lead to novel therapeutic targets and more effective vaccines.…”
Section: Immune Responses and Disease Control And Preventionmentioning
confidence: 99%
“…IPEC-DQ cell line was a gift from Dr. Dongwan Yoo, University of Illinois at Urbana-Champaign, Urbana IL, USA. It was a subclone of IPEC-J2 cells, a porcine small intestinal cell line, and maintained in Roswell Park Memorial Institute 1640 Medium (RPMI-1640, Gibco) supplemented with 10% FBS and 1% penicillin/streptomycin (Zhang et al, 2018b). For virus propagation in IPEC-DQ cells, maintenance medium was RPMI-1640 containing 0.3% TPB, 1% Penicillin/Streptomycin and 1 μg/mL trypsin.…”
Section: Cell Lines Recombinant Viruses Reagents and Antibodiesmentioning
confidence: 99%
“…Vero cells are the most commonly used cell line for PEDV isolation and propagation (Teeravechyan et al, 2016). IPEC-DQ cell is a subclone of porcine small intestinal cell line IPEC-J2 (Zhang et al, 2018b). Although PEDV grows less efficiently in IPEC-DQ cells than in Vero cells, PEDV infection of IPEC-DQ cells is more relevant physiologically to PEDV natural infection in the intestines of pigs.…”
Section: Introductionmentioning
confidence: 99%